2009
DOI: 10.1021/jo802473p
|View full text |Cite
|
Sign up to set email alerts
|

p-Nitrophenolate: A Probe for Determining Acid Strength in Ionic Liquids

Abstract: In order to obtain an acidity scale in room-temperature ionic liquid solutions, the protonation equilibrium of sodium p-nitrophenolate in [bm(2)im][NTf(2)] and in [bmpyrr][NTf(2)], at 298 K, has been studied by means of spectrophotometric titration. Carboxylic acids differing in both structure and in water solution strength have been used. Data collected indicate that in the analyzed ionic liquid solutions carboxylic acids are less dissociated than in water solution. Furthermore, by virtue of a mutual interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 55 publications
4
37
2
Order By: Relevance
“…It is noteworthy that due to the high viscosity of [Bmim]PF 6 , the pKa of these amines could not be determined in this IL by the method described previ-ously by us [16]. Therefore, we determined the relative basicity constant (K R ) of these amines in [Bmim]PF 6 by using a method described by D'anna et al [15], which has shown a good correlation between the pKa and log K R for these amines in ILs [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that due to the high viscosity of [Bmim]PF 6 , the pKa of these amines could not be determined in this IL by the method described previ-ously by us [16]. Therefore, we determined the relative basicity constant (K R ) of these amines in [Bmim]PF 6 by using a method described by D'anna et al [15], which has shown a good correlation between the pKa and log K R for these amines in ILs [13].…”
Section: Resultsmentioning
confidence: 99%
“…The K R values of SA amines in [Bmim]PF 6 were determined by using the method described by D'anna et al [15]. The method consist of determination of the basic strength of amines in ILs by means of the formation of amine/p-nitrophenol ion pairs through UV-vis measurements employing 4-nitrophenol as reference.…”
Section: Determination Of the Relative Basicity Constant (K R ) Of Samentioning
confidence: 99%
“…The inclusion of water and acid in IL influences the potential window and ultimate reduction potential that is achievable in electrochemical experiments 9,13. The dissolution of metal oxides and carbonates can produce IL solutions that contain added water and leave residual acid 19,20. Furthermore, both unreacted and partially dissociated acid are present in both the IL and water.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical species, bis(trifluoromethanesulfonyl)imide [HTFSI], was utilized to provide a common acid species in ILs that contain the bis(trifluoromethanesulfonyl)imide anion [TFSI − ]. Although the evolution of hydrogen at gold and platinum in the ionic liquid N ‐trimethyl‐ N ‐butylammonium bis(trifluoromethanesulfonyl)imide [Me 3 N n Bu][TFSI] containing HTFSI has been achieved, the results indicate that the acid is only partially dissociated 19,20. However, increasing the water concentration enhanced the proton dissociation and the acid strength, increasing the solubility of the metal species in the IL.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity strength of an acid can be expressed by Hammett function using UV-visible spectrophotometry. For example, the acidity measurement of nonchloroaluminate ILs had been performed successfully utilizing UV-visible spectroscopy with Hammett indicator method [20], and this method was applied to determine the acidity of protic pyridinium ILs, Brønsted acidic ILs, and the strength of carboxylic acids in different ILs [21][22][23][24].…”
Section: Acidity Determination Of the Ilsmentioning
confidence: 99%